Performance Based Design: Performance Analysis on Fixed Base Structure and Structures with High Damping Rubber Bearing (HDRB) - Maulida, Alfia Salma Mei; Umniati, B. Sri; Sulton, Mohammad; Maulidani, Andra Akmal (Universitas Islam 45, 2025)
Buildings in Malang City face large lateral load from earthquakes due to seismic activity. One method of reducing the lateral load is to use base isolators. Conventional building design resists lateral load by designing buildings to be elastic or rigid with Strength Based Design criteria. However, elasticity results in larger building elements, stiffness increases the building's exposure to earthquake forces, and Strength Based Design is unreliable in shielding from earthquakes since its recommended to be a minimum design criterion by FEMA P-424. Therefore, more comprehensive design criteria such as Performance Based Design are needed. The objective of this study is to assess the analysis results and performance levels of fixed base structure compared to structures with HDRB, including the effect of rubber thickness and shear modulus. This study starts by modeling a 7-story building with a fixed base structure using ETABS. The results were then used to determine the type of HDRB, from two models with different rubber thickness and shear modulus, for modeling structures with HDRB. Furthermore, the running results of the two structures are analyzed to evaluate the level of performance of the structures based on Performance Based Design criteria. The results showed differences with the reduction of the average period value by 91.51%, the base shear as 36.05% and 33.11% in longitudinal and transverse direction respectively, and the average interstory drift as 54.86% in X-axis and 31.17% Y-axis. The target displacement of the structures with HDRB decreases and the performance levels including the analysis results are improved.